CA / PANI / ZnO nanomaterial, gas sensitive element and QCM ammonia sensor and preparation method and application thereof
By using the QCM ammonia sensor prepared by CA/PANI/ZnO nanomaterials, the problems of insufficient ammonia detection sensitivity and slow response speed in the prior art are solved, and fast and accurate detection of low-concentration ammonia is achieved.
Patent Information
- Application Number
- CN202310250890.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-16
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-03-16
AI Technical Summary
The existing ammonia detection methods have problems such as insufficient sensitivity, slow response speed and low selectivity, making it difficult to effectively detect low-concentration ammonia.
CA/PANI/ZnO nanomaterials were used as sensor-sensitive membrane materials, and multi-porous, high specific surface area, laminated and staggered incompletely coated structures were synthesized by combining electrospinning, oxidative polymerization and one-step thermal solvent method to prepare QCM ammonia sensors.
It achieves rapid response and recovery to ammonia (15s/10s), has a sensitivity of 5.47Hz/ppm, has good repeat response characteristics and selectivity, and can effectively detect low-concentration ammonia at room temperature.
Smart Images

Figure CN116239824B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ammonia sensors, and in particular to a CA / PANI / ZnO nanomaterial, a gas sensitive element and a QCM ammonia sensor, as well as a preparation method and application thereof. Background Art
[0002] With the further development of industry, the problem of air pollution has become more and more serious. From the perspective of people's livelihood, health and environmental protection, it is particularly important to monitor polluted gases. Ammonia is a colorless gas with a strong pungent odor. It is widely present in the fields of chemical industry and agriculture. Due to its extremely high solubility, it will irritate and corrode the human respiratory tract when inhaled, thereby weakening the body's resistance to disease. When the inhaled concentration is too high, it will also affect the reflex action of the trigeminal nerve endings and cause cardiac arrest and respiratory arrest. The U.S. Occupational Safety and Health Administration stipulates that the maximum limit concentration of ammonia that the human body is exposed to within 15 minutes is an average of 35ppm, and an average of 25ppm within 8 hours. In summary, the preparation of high-performance ammonia sensors is of great practical significance.
[0003] Quartz crystal microbalance (QCM) has attracted wide attention in ammonia detection due to its advantages of high precision, low power consumption and high stability. Its detection mechanism is: the sensitive film adsorbs gas molecules, and the mass change changes the resonant frequency of the quartz crystal, thereby collecting the frequency output of the QCM. Therefore, the nanomaterials that constitute the sensitive film are the key to QCM detection of ammonia. Polyaniline (PANI) is a typical representative of ammonia polymer sensing layer. It has the advantages of high conductivity, high environmental stability, low cost and easy polymerization. It has been widely used in the field of ammonia detection in recent years. Recent studies have shown that due to the strong interaction between Lewis acid and base, sensitive materials doped with organic acids can significantly improve the sensitivity and selectivity of ammonia detection and show excellent ammonia response. In addition, the inorganic material zinc oxide has attracted much attention due to its non-toxicity, good biocompatibility, strong electron transfer ability, high chemical stability and good mechanical strength. In particular, it has been reported that the hybrid structure of PANI and ZnO has a much higher gas-sensitive response to ammonia than single ZnO. To this end, we selected electrospun cellulose acetate (CA) as the scaffold of PANI to improve its mechanical stability and doped it with zinc oxide nanoflowers (ZnO NF) to change its structure and produce more active sites to compensate for these problems. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the above-mentioned ammonia detection method, establish a QCM ammonia sensor with CA / PANI / ZnO as the sensor sensitive membrane material and based on the dual crystal oscillator difference frequency output signal, and its preparation method and application, with fast response and recovery speed (15s / 10s), and sensitivity of 5.47ppm / Hz, with good repeated response characteristics and selectivity, and the QCM ammonia sensor is fast, continuous and repeatable, and can realize effective detection of low-concentration ammonia at room temperature.
[0005] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a CA / PANI / ZnO nanomaterial, which is synthesized by a combination of electrospinning, oxidative polymerization and a one-step hot solvent method to form a CA / PANI fibrous nanostructure assisted by ZnO nanoflowers, and the overall structure is porous, high in specific surface area, and has a stacked and staggered incomplete coating structure.
[0006] A method for preparing a CA / PANI / ZnO nanomaterial comprises the following steps:
[0007] ①Preparation of CA nanofiber precursors:
[0008] The cellulose acetate powder is dissolved in a mixed solvent of acetone and DMAc, and stirred at 50-70° C. for 1-2 hours to obtain a viscous electrospinning precursor solution with a mass fraction of about 13-16%.
[0009] ② The precursor solution obtained in ① was subjected to an electrospinning process, and the electrospinning time was fixed at 1 to 3 h, and finally white CA nanofibers were deposited on a roller with tin foil attached;
[0010] ③ Preparation of CA / PANI composite nanofibers by oxidative polymerization:
[0011] Slowly add concentrated hydrochloric acid to the dispersed CA nanofiber solution and stir thoroughly, add aniline monomer solution drop by drop to the above solution, transfer the mixed solution to a water bath at 0-5°C and stir, then slowly add drop by drop to the DMAc solution containing APS, continue magnetic stirring for 2-3h, centrifuge the obtained dark green solution and wash with ethanol, dry the obtained sample in a vacuum drying oven at 60-80°C overnight to obtain CA / PANI composite nanofibers;
[0012] ④ Obtain 3D self-assembled ZnO NF using a one-step solvothermal method:
[0013] Zinc acetate dihydrate, ethanol and triethanolamine were added to deionized water respectively while magnetic stirring, and after stirring for 1 hour, the colorless transparent mixed solution was transferred to a polytetrafluoroethylene-lined reactor and reacted at 170°C for 24 hours; after the reaction was completely cooled to room temperature naturally, the solution was centrifuged and washed and dried with ethanol, ZnO was weighed and dissolved in a buffer solution, and magnetic stirring was performed for 10 to 30 minutes to mix evenly;
[0014] ⑤ Add the dark green CA / PANI composite nanofibers obtained in ③ to the white ZnO solution obtained in ④, and then keep the solution at 20-30°C in the dark for 24 hours to finally obtain a CA / PANI / ZnO mixed solution;
[0015] ⑥ Wash the dark green product obtained in ⑤ with water and dry it to obtain the CA / PANI / ZnO nanomaterial.
[0016] Furthermore,
[0017] The volume ratio of acetone to DMAc in ① is 2:1.
[0018] Furthermore,
[0019] The electrospinning process in ② is as follows: use a 15mL syringe to absorb 7mL of the precursor solution obtained in ①, connect a No. 23 metal needle to the front end and connect it to a high-voltage power supply for electrospinning, and set the distance between the roller and the metal needle to 15cm; the voltage applied at both ends is 18kV; the feed rate is 0.18-0.24mL / h; and the roller rotation rate is 60rpm.
[0020] Furthermore,
[0021] The volume ratio of the concentrated hydrochloric acid, CA nanofiber solution, aniline monomer solution and DMAc solution in ③ is 190:2500:9:1800; the concentration of APS is 14 g / mL; the number of ethanol washings is 3 to 5 times, the drying temperature is 55 to 65° C., and the drying time is 12 to 24 hours;
[0022] Or, in said ④, the mass ratio of zinc acetate dihydrate to ZnO is 5:4, the volume ratio of ethanol, triethanolamine and deionized water is 2:1:3, and 5 mg of zinc acetate dihydrate is added to each milliliter of deionized water.
[0023] Furthermore, 150 g CA / PANI composite nanofibers are added to each ml ZnO white solution in ⑤;
[0024] Or, the number of water washing in said ⑥ is 4 to 6 times, the drying temperature is 60 to 80° C., and the drying time is 12 to 24 hours.
[0025] A gas sensor is provided with a gas-sensitive coating, wherein the gas-sensitive coating has the above-mentioned material or is prepared according to the above-mentioned method.
[0026] A QCM ammonia sensor is provided with a gas-sensitive coating, and the gas-sensitive coating is attached to the outer surface of a silver electrode of a quartz crystal microbalance.
[0027] Furthermore,
[0028] The CA / PANI / ZnO nanomaterials were added to anhydrous ethanol and ultrasonically vibrated for 10 to 20 minutes to obtain a homogeneous solution. 2 to 10 μL was transferred to the surface of the silver electrode of the quartz crystal microbalance, and the CA / PANI / ZnO nanomaterials were evenly coated on the surface of the silver electrode of the quartz crystal microbalance using a spin coater. The solution was dried in a dryer at room temperature of 20 to 30°C for 12 to 24 hours, and a QCM ammonia sensor was prepared by collecting the difference frequency signal based on the difference frequency output of the dual crystal oscillator.
[0029] Application of QCM ammonia sensor, the sensor is used to detect ammonia.
[0030] The benefits of the CA / PANI / ZnO nanomaterial, gas sensor and QCM ammonia sensor of the present invention and their preparation methods and applications are as follows:
[0031] (1) The present invention synthesizes CA / PANI fibrous nanostructures assisted by ZnO nanoflowers by combining simple electrospinning, oxidative polymerization and a one-step hot solvent method. The overall structure is porous, high in specific surface area, and stacked and staggered incompletely coated. At the same time, the ester group and amino group of the CA / PANI fiber structure itself and the large number of active sites existing in ZnO are beneficial to improving the adsorption capacity of ammonia.
[0032] (2) The present invention uses a spin coating method to uniformly coat the CA / PANI / ZnO nanomaterials on the silver electrode surface of the quartz crystal microbalance, and then dries it at room temperature of 20 to 30°C to obtain a quartz crystal microbalance ammonia sensor with a CA / PANI / ZnO nanocomposite film. The sensor has a maximum sensitivity of 5.47 Hz / ppm to ammonia molecules at room temperature, has a fast response / recovery time (15s / 10s), high linearity, excellent repeatability and selectivity, and provides a feasible solution for achieving high-precision ammonia detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Schematic diagram of the structure of a quartz crystal microbalance (QCM) in the example, wherein reference numeral 1 represents an AT-type quartz crystal substrate, 2 represents a silver electrode, 3 represents a gas-sensitive film, 4 represents a base, and 5 represents an electrode lead;
[0034] Figure 2 is the X-ray diffraction pattern of the CA / PANI composite nanomaterial assisted by ZnO in Example 1;
[0035] Figure 3 is a dynamic response curve diagram of the gas sensor in Example 1 to different concentrations of ammonia;
[0036] Figure 4 is a continuous response curve diagram of the gas sensor in Example 1 to the gradually increasing concentration of ammonia;
[0037] Figure 5 is a linear fitting diagram of the gas sensor in Example 1 in response to ammonia concentration and frequency;
[0038] Figure 6 The graph is a response and recovery time graph of the gas sensor in Example 1 to 30 ppm ammonia;
[0039] Figure 7 The reproducibility curve of the gas sensor in Example 1 to 1, 10, 30, 50, and 70 ppm ammonia;
[0040] Figure 8 This is a long-term stability test of the gas sensor in Example 1 within one month;
[0041] Fig. 9 (a) is the conductivity spectra of the gas sensor in Example 1 to different concentrations of ammonia, (b) is the relationship between ammonia concentration and quality factor;
[0042] Fig.10 The selectivity diagram of the gas sensor in Example 1 to different types of gases at 30 ppm; DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0044] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0045] Example 1
[0046] A gas sensor based on a quartz crystal microbalance (QCM) surface coated with ZnO nanoflowers assisted CA / PANI fiber nanomaterials, the gas sensor is provided with a gas-sensitive coating of CA / PANI / ZnO nanomaterials, and its structural schematic diagram is shown in FIG. Figure 1 As shown. Prepare a clean quartz crystal microbalance, including an AT-type quartz wafer substrate 1 and two circular silver electrode sheets 2 respectively located on the two surfaces of the quartz wafer, an external base 4, and two electrode leads 5. The quartz crystal microbalance has the following specifications: the crystal diameter is 8mm, the resonant frequency is 8MHz, and the silver electrode diameter is 5mm. The gas sensor has a concentration detection range of 1ppm to 70ppm for ammonia.
[0047] A CA / PANI / ZnO nanomaterial is synthesized by combining electrospinning, oxidative polymerization and a one-step hot solvent method to form a CA / PANI fibrous nanostructure assisted by ZnO nanoflowers. The overall structure is porous, high specific surface area, and stacked and staggered incomplete coating.
[0048] The X-ray diffraction pattern of CA / PANI fiber nanomaterials assisted by ZnO nanoflowers is shown in Figure 2 As shown, the prepared ZnO nanoflowers show a typical hexagonal wurtzite structure with good crystallization. After compounding with CA / PANI, it was observed that all diffraction peaks of the CA / PANI / ZnO composite material can be indexed from CA, PANI and ZnO, and there are no impurity peaks, indicating that CA, PANI and ZnO are successfully compounded.
[0049] A method for preparing ZnO nanoflower-assisted CA / PANI fibrous nanomaterials is carried out according to the following steps:
[0050] ① Preparation of CA nanofiber precursor: 2.2 g of cellulose acetate powder was dissolved in 15 mL of a solvent of acetone and DMAc in a volume ratio of 2:1, and stirred at 50 °C for 1 h to obtain a viscous electrospinning precursor solution with a mass fraction of about 13%.
[0051] ② The precursor solution obtained in step ① was subjected to an electrospinning process, and the electrospinning time was fixed at 1 h, and finally white CA nanofibers were deposited on a roller with tin foil attached.
[0052] ③ Use the oxidative polymerization method to prepare CA / PANI composite nanofibers. Slowly add 1.7mL of concentrated hydrochloric acid to the dispersed 15mL CA nanofiber solution and stir thoroughly, add 70uL of aniline monomer solution drop by drop to the above solution, transfer the mixed solution to a 0-5℃ water bath and stir after the addition is complete, then slowly add 12mL of DMAc solution containing 0.15g of APS drop by drop, continue magnetic stirring for 2h, centrifuge the obtained dark green solution and wash it with ethanol several times 3 times, and dry the obtained sample in a vacuum drying oven at 60℃ overnight to obtain CA / PANI composite nanofibers.
[0053] ④ A one-step solvothermal method was used to obtain 3D self-assembled ZnO NF. 0.15 g zinc acetate dihydrate, 20 mL ethanol and 10 mL triethanolamine were added to 30 mL deionized water while magnetic stirring. After stirring for 1 h, the colorless and transparent mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined reactor and reacted at 170 ° C for 24 h. After the reaction was completely cooled to room temperature naturally, the solution was centrifuged and washed and dried with ethanol three times. 0.08 g of ZnO was weighed and dissolved in the buffer solution, and magnetic stirring was performed for 10 min to mix evenly.
[0054] ⑤ Add the dark green CA / PANI composite nanofibers obtained in step ③ to the white ZnO solution obtained in step ④, the ratio of the volume (mL) of the buffer solution to the mass (g) of the CA / PANI composite nanofibers is 100, and then keep the solution in a dark place at 20-30°C for 24 hours to finally obtain a CA / PANI / ZnO mixed solution.
[0055] ⑥ The dark green product obtained in step ⑤ was washed with water 4 times and dried at 60° C. for 24 h to obtain the CA / PANI / ZnO nanomaterial.
[0056] A QCM ammonia sensor is provided. The CA / PANI fiber nanomaterial assisted by ZnO nanoflowers is added to anhydrous ethanol, and ultrasonically vibrated for 10 minutes to obtain a homogeneous solution; 2 μL is transferred to the surface of a crystal oscillator electrode, and the CA / PANI / ZnO composite nanomaterial is evenly coated on the surface of the quartz crystal microbalance using a spin coater, so as to be arranged on at least a portion of the silver electrode. The solution is placed in a dryer at room temperature of 20 to 30°C and dried for 12 hours, and a QCM ammonia sensor is prepared by a method of collecting difference frequency signals based on the difference frequency output of a dual crystal oscillator.
[0057] The dynamic response results of the quartz crystal microbalance ammonia sensor based on ZnO nanoflower-assisted CA / PANI nanomaterials to different ammonia concentrations are shown in Figure 2. Figure 3 As shown in the figure, the frequency response of the QCM sensor increases with the increase of ammonia concentration. The frequency responses of 1, 10, 30, 50 and 70 ppm ammonia are 50.36, 117.09, 180.7, 263.94 and 382.61 Hz, respectively, indicating that the quartz crystal microbalance sensor based on CA / PANI / ZnO nanomaterials can be used for lower concentration ammonia gas detection. Figure 4 The continuous response curve of the sensor to the gradually increasing concentration of ammonia is given. It can be seen from the figure that the frequency change level is Figure 3 The dynamic response results are basically consistent.
[0058] Based on the dynamic response results of the quartz crystal microbalance sensor under 1-70ppm ammonia, Figure 5 The linear fitting diagram of ammonia concentration and frequency response is given. It can be seen from the figure that the linear fitting equation is Δf = -56.87-4.54x, and the correlation coefficient is 0.9827, which shows that the gas sensor has good linearity.
[0059] Figure 6 The graph shows the response and recovery time curve of the quartz crystal microbalance sensor based on CA / PANI / ZnO nanomaterials to 30ppm ammonia. As can be seen from the figure, the adsorption time of the gas sensor to ammonia is 15s, and the desorption time is 10s. This shows that after CA / PANI and ZnO are composited, they have excellent response / recovery capabilities to ammonia, which is also the greatest advantage of the present invention.
[0060] Figure 7 The graph shows the reproducibility of the gas sensor of the present invention to 1, 10, 30, 50, and 70 ppm ammonia. As can be seen from the graph, the gas sensor is sequentially exposed to the test environment of 1 to 70 ppm ammonia, and each concentration gradient is continuously cycled 3 times. The results show that the gas sensor has good response repeatability to different concentrations of ammonia.
[0061] Figure 8 The figure shows the long-term stability test of the gas sensor of the present invention. It can be seen from the figure that the gas sensor has good response stability to various concentrations of ammonia within 30 days.
[0062] Fig. 9 (a) shows the conductivity spectra of the gas sensor of the present invention for different concentrations of ammonia. It can be seen from the figure that with the increase of ammonia concentration, the resonance frequency of the quartz crystal microbalance shows a downward trend, and the frequency shift corresponds to the above frequency response results. The quality factor (Q) is defined as the ratio of the peak frequency to the half bandwidth of the corresponding conductivity spectrum. The stability and anti-interference ability of the QCM gas sensor will increase with the increase of the Q value. Fig. 9 (b) shows the relationship between ammonia concentration and quality factor. It can be seen from the figure that the gas sensor has a high Q value in various ammonia concentration environments, which indicates that the gas sensor of the present invention has high stability.
[0063] Fig.10 The selectivity test of the gas sensor of the present invention to different types of gases at 30ppm is shown in the figure. As can be seen from the figure, under the same detection conditions, the frequency response capability of the gas sensor of the present invention to ammonia is significantly higher than that of other gases, indicating an ultra-high selectivity to ammonia.
[0064] The ammonia sensor of the present invention has good repeatability, fast response and recovery speed (15s / 10s), high sensitivity (5.47Hz / ppm), stable performance, can be used for the effective detection of ammonia as low as 1ppm, and has good application prospects.
[0065] Example 2
[0066] A QCM ammonia sensor with ZnO nanoflower-assisted CA / PANI fiber nanocomposite as gas-sensitive film, the structural schematic diagram of which is shown in FIG. Figure 1 shown.
[0067] A method for preparing ZnO nanoflower-assisted CA / PANI fibrous nanomaterials is carried out according to the following steps:
[0068] ① Preparation of CA nanofiber precursor: 2.3 g of cellulose acetate powder was dissolved in 15 mL of a solvent of acetone and DMAc in a volume ratio of 2:1, and stirred at 60 °C for 1.5 h to finally obtain a viscous electrospinning precursor solution with a mass fraction of about 14.5%.
[0069] ② The precursor solution obtained in step ① was subjected to an electrospinning process, and the electrospinning time was fixed at 2 h. Finally, white CA nanofibers were deposited on a roller with tin foil attached.
[0070] ③ Use the oxidative polymerization method to prepare CA / PANI composite nanofibers. Slowly add 1.8mL of concentrated hydrochloric acid to the dispersed 20mL CA nanofiber solution and stir thoroughly, add 80uL of aniline monomer solution drop by drop to the above solution, transfer the mixed solution to a 0-5℃ water bath and stir after the addition is complete, then slowly add 15mL of DMAc solution containing 0.20g of APS drop by drop, continue magnetic stirring for 2.5h, centrifuge the obtained dark green solution and wash it with ethanol several times 4 times, and dry the obtained sample in a vacuum drying oven at 70℃ overnight to obtain CA / PANI composite nanofibers.
[0071] ④ Obtain 3D self-assembled ZnO NF by one-step solvothermal method. Add 0.15g zinc acetate dihydrate, 20mL ethanol and 10mL triethanolamine to 30mL deionized water while magnetic stirring. After stirring for 1h, transfer the colorless transparent mixed solution to a 100mL polytetrafluoroethylene-lined reactor and react at 170℃ for 24h. After the reaction is completely cooled to room temperature naturally, the solution is centrifuged and washed and dried with ethanol three times. Weigh 0.10g of ZnO and dissolve it in the buffer solution. Stir magnetically for 20min to mix evenly.
[0072] ⑤ Add the dark green CA / PANI composite nanofibers obtained in step ③ to the white ZnO solution obtained in step ④, the ratio of the volume (mL) of the buffer solution to the mass (g) of the CA / PANI composite nanofibers is 120, and then place the solution in a dark place at 20-30°C for 24 hours to finally obtain a CA / PANI / ZnO mixed solution.
[0073] A QCM ammonia sensor is provided. The CA / PANI fiber nanomaterial assisted by ZnO nanoflowers is added to anhydrous ethanol, and ultrasonically vibrated for 15 minutes to obtain a homogeneous solution; 5 μL is transferred to the surface of a crystal electrode, and the CA / PANI / ZnO composite nanomaterial is evenly coated on the surface of the quartz crystal microbalance using a spin coater, so as to be arranged on at least a portion of the silver electrode. The solution is placed in a dryer at room temperature of 20 to 30°C and dried for 18 hours, and a QCM ammonia sensor is prepared by a method of collecting difference frequency signals based on the difference frequency output of a dual crystal oscillator.
[0074] After testing, it was found that the QCM gas sensor prepared in this embodiment with the ZnO nanoflower-assisted CA / PANI fiber nanocomposite material as the gas-sensitive film had good gas-sensitive sensing performance for ammonia gas with a concentration of 1ppm to 70ppm.
[0075] Example 3
[0076] A QCM gas sensor with ZnO nanoflower-assisted CA / PANI fiber nanocomposite as gas-sensitive film, the structural schematic diagram of which is shown in FIG. Figure 1 shown.
[0077] A method for preparing ZnO nanoflower-assisted CA / PANI fibrous nanomaterials is carried out according to the following steps:
[0078] ① Preparation of CA nanofiber precursor: 2.4 g of cellulose acetate powder was dissolved in 15 mL of a solvent of acetone and DMAc in a volume ratio of 2:1, and stirred at 70 °C for 2 h to obtain a viscous electrospinning precursor solution with a mass fraction of about 16%.
[0079] ② The precursor solution obtained in step ① was subjected to an electrospinning process, and the electrospinning time was fixed at 3 h. Finally, white CA nanofibers were deposited on a roller with tin foil attached.
[0080] ③ Use the oxidative polymerization method to prepare CA / PANI composite nanofibers. Slowly add 1.9mL of concentrated hydrochloric acid to the dispersed 25mL CA nanofiber solution and stir thoroughly, add 90uL of aniline monomer solution drop by drop to the above solution, transfer the mixed solution to a 0-5℃ water bath and stir after the addition is complete, then slowly add 18mL of DMAc solution containing 0.25g of APS drop by drop, continue magnetic stirring for 3h, centrifuge the obtained dark green solution and wash it with ethanol several times 5 times, and dry the obtained sample in a vacuum drying oven at 80℃ overnight to obtain CA / PANI composite nanofibers.
[0081] ④ A one-step solvothermal method was used to obtain 3D self-assembled ZnO NF. 0.15 g zinc acetate dihydrate, 20 mL ethanol and 10 mL triethanolamine were added to 30 mL deionized water while magnetic stirring. After stirring for 1 h, the colorless and transparent mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined reactor and reacted at 170 ° C for 24 h. After the reaction was completely cooled to room temperature naturally, the solution was centrifuged and washed and dried with ethanol three times. 0.12 g of ZnO was weighed and dissolved in the buffer solution, and magnetic stirring was performed for 30 min to mix evenly.
[0082] ⑤ Add the dark green CA / PANI composite nanofibers obtained in step ③ to the white ZnO solution obtained in step ④, the ratio of the volume (mL) of the buffer solution to the mass (g) of the CA / PANI composite nanofibers is 150, and then keep the solution in a dark place at 20-30°C for 24 hours to finally obtain a CA / PANI / ZnO mixed solution.
[0083] A QCM ammonia sensor is provided. The CA / PANI fiber nanomaterial assisted by ZnO nanoflowers is added to anhydrous ethanol, and ultrasonically vibrated for 15 minutes to obtain a homogeneous solution; 8 μL is transferred to the surface of a crystal oscillator electrode, and the CA / PANI / ZnO composite nanomaterial is evenly coated on the surface of the quartz crystal microbalance using a spin coater, so as to be arranged on at least a portion of the silver electrode. The solution is placed in a dryer at room temperature of 20 to 30°C and dried for 24 hours, and a QCM ammonia sensor is prepared by a method of collecting difference frequency signals based on the difference frequency output of a dual crystal oscillator.
[0084] After testing, it was found that the QCM gas sensor prepared in this embodiment with the ZnO nanoflower-assisted CA / PANI fiber nanocomposite material as the gas-sensitive film had good gas-sensitive sensing performance for ammonia gas with a concentration of 1ppm to 70ppm.
[0085] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable ordinary technicians in the field to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made based on the essence of the content of the present invention should be included in the protection scope of the present invention.
Claims
1. A CA / PANI / ZnO nanomaterial, characterized in that: The preparation method thereof comprises the following steps: ①Preparation of CA nanofiber precursors: The cellulose acetate powder is dissolved in a mixed solvent of acetone and DMAc, and stirred at 50-70° C. for 1-2 hours to obtain a viscous electrospinning precursor solution with a mass fraction of 13-16%. ② The precursor solution obtained in ① was subjected to an electrospinning process, and the electrospinning time was fixed at 1 to 3 h, and finally white CA nanofibers were deposited on a roller with tin foil attached; ③ Preparation of CA / PANI composite nanofibers by oxidative polymerization: Slowly add concentrated hydrochloric acid to the dispersed CA nanofiber solution and stir thoroughly, add aniline monomer solution drop by drop to the above solution, transfer the mixed solution to a water bath at 0-5°C and stir, then slowly add drop by drop to the DMAc solution containing APS, continue magnetic stirring for 2-3h, centrifuge the obtained dark green solution and wash with ethanol, dry the obtained sample in a vacuum drying oven at 60-80°C overnight to obtain CA / PANI composite nanofibers; ④ Obtain 3D self-assembled ZnO NF using a one-step solvothermal method: Zinc acetate dihydrate, ethanol and triethanolamine were added to deionized water respectively while magnetic stirring, and after stirring for 1 hour, the colorless transparent mixed solution was transferred to a polytetrafluoroethylene-lined reactor and reacted at 170°C for 24 hours; after the reaction was completely cooled to room temperature naturally, the solution was centrifuged and washed and dried with ethanol, ZnO was weighed and dissolved in a buffer solution, and magnetic stirring was performed for 10 to 30 minutes to mix evenly; ⑤ Add the dark green CA / PANI composite nanofibers obtained in ③ to the white ZnO solution obtained in ④, and then keep the solution at 20-30°C in the dark for 24 hours to finally obtain a CA / PANI / ZnO mixed solution; ⑥ Wash the dark green product obtained in ⑤ with water and dry it to obtain the CA / PANI / ZnO nanomaterial.
2. A method for preparing the CA / PANI / ZnO nanomaterial according to claim 1, characterized in that: The steps include: ①Preparation of CA nanofiber precursors: The cellulose acetate powder is dissolved in a mixed solvent of acetone and DMAc, and stirred at 50-70° C. for 1-2 hours to obtain a viscous electrospinning precursor solution with a mass fraction of 13-16%. ② The precursor solution obtained in ① was subjected to an electrospinning process, and the electrospinning time was fixed at 1 to 3 h, and finally white CA nanofibers were deposited on a roller with tin foil attached; ③ Preparation of CA / PANI composite nanofibers by oxidative polymerization: Slowly add concentrated hydrochloric acid to the dispersed CA nanofiber solution and stir thoroughly, add aniline monomer solution drop by drop to the above solution, transfer the mixed solution to a water bath at 0-5°C and stir, then slowly add drop by drop to the DMAc solution containing APS, continue magnetic stirring for 2-3h, centrifuge the obtained dark green solution and wash with ethanol, dry the obtained sample in a vacuum drying oven at 60-80°C overnight to obtain CA / PANI composite nanofibers; ④ Obtain 3D self-assembled ZnO NF using a one-step solvothermal method: Zinc acetate dihydrate, ethanol and triethanolamine were added to deionized water respectively while magnetic stirring, and after stirring for 1 hour, the colorless transparent mixed solution was transferred to a polytetrafluoroethylene-lined reactor and reacted at 170°C for 24 hours; after the reaction was completely cooled to room temperature naturally, the solution was centrifuged and washed and dried with ethanol, ZnO was weighed and dissolved in a buffer solution, and magnetic stirring was performed for 10 to 30 minutes to mix evenly; ⑤ Add the dark green CA / PANI composite nanofibers obtained in ③ to the white ZnO solution obtained in ④, and then keep the solution at 20-30°C in the dark for 24 hours to finally obtain a CA / PANI / ZnO mixed solution; ⑥ Wash the dark green product obtained in ⑤ with water and dry it to obtain the CA / PANI / ZnO nanomaterial.
3. The method for preparing the CA / PANI / ZnO nanomaterial according to claim 2, characterized in that: The volume ratio of acetone to DMAc in ① is 2:
1.
4. The method for preparing the CA / PANI / ZnO nanomaterial according to claim 2, characterized in that: The electrospinning process in ② is as follows: use a 15mL syringe to absorb 7mL of the precursor solution obtained in ①, connect a No. 23 metal needle to the front end and connect it to a high-voltage power supply for electrospinning, and set the distance between the roller and the metal needle to 15cm; the voltage applied at both ends is 18kV; the feed rate is 0.18-0.24mL / h; and the roller rotation rate is 60rpm.
5. The method for preparing the CA / PANI / ZnO nanomaterial according to claim 2, characterized in that: The volume ratio of the concentrated hydrochloric acid, CA nanofiber solution, aniline monomer solution and DMAc solution in ③ is 190:2500:9:1800; the concentration of APS is 14 g / mL; the number of ethanol washings is 3 to 5 times, the drying temperature is 55 to 65° C., and the drying time is 12 to 24 hours; Or, in said ④, the mass ratio of zinc acetate dihydrate to ZnO is 5:4, the volume ratio of ethanol, triethanolamine and deionized water is 2:1:3, and 5 mg of zinc acetate dihydrate is added to each milliliter of deionized water.
6. The method for preparing the CA / PANI / ZnO nanomaterial according to claim 2, characterized in that: In said ⑤, 150 g CA / PANI composite nanofibers are added per ml ZnO white solution; Or, the number of water washing in said ⑥ is 4 to 6 times, the drying temperature is 60 to 80° C., and the drying time is 12 to 24 hours.
7. A gas sensor, characterized in that: The gas-sensitive element is provided with a gas-sensitive coating, and the gas-sensitive coating has the material according to claim 1, or is prepared according to the method according to any one of claims 2-6.
8. A QCM ammonia sensor, characterized in that: The sensor is provided with a gas-sensitive coating, the gas-sensitive coating having the material according to claim 1 or being prepared according to the method according to any one of claims 2 to 6, and the gas-sensitive coating is attached to the outer surface of the silver electrode of the quartz crystal microbalance.
9. The method for preparing the QCM ammonia sensor according to claim 8, characterized in that: The CA / PANI / ZnO nanomaterials were added to anhydrous ethanol and ultrasonically vibrated for 10 to 20 minutes to obtain a homogeneous solution; 2 to 10 μL were transferred to the surface of the silver electrode of the quartz crystal microbalance, and the CA / PANI / ZnO nanomaterials were evenly coated on the surface of the silver electrode of the quartz crystal microbalance using a spin coater, and the solution was dried in a dryer at room temperature of 20 to 30°C for 12 to 24 hours to prepare a QCM ammonia sensor based on the method of collecting difference frequency signals based on the difference frequency output of the dual crystal oscillator.
10. The use of the QCM ammonia sensor according to claim 8, or the sensor prepared by the method according to claim 9, characterized in that: The sensor is used to detect ammonia.
Citation Information
Patent Citations
Method for preparing polyaniline nanofiber / cellulose diacetate composite conductive material
CN103965513A
QCM (Quartz Crystal Microbalance) humidity-sensitive sensor based on cellulose acetate / konjac glucomannan film as well as construction method and application of QCM humidity-sensitive sensor
CN115266912A